Factors that influence in the adherence to treatments in patients with risk for cardiovascular disease (2010)
A descriptive-methodological research was carried out on the factors that influence the adherence to pharmacologic and non-pharmacologic treatments of 262 patients with risk factors for cardiovascular disease of the Caja de Previsión Social of the University of Cartagena, and the facial validity and the reliability of the instrument used was determined. The results of the facial validity of the instrument designed by Bonilla and De Reales indicated that of the initial version of 72 items, 22 required modifications and 15 were eliminated; the proposal to redesign the instrument was left with a total of 57 items; of this proposal the authors accepted to eliminate only 10 items. The new version of the instrument had a total of 62 items, which reported an alpha of Cronbach of 0,797 and was used to describe the factors that influence on the adherence. Of the total of patients with risk factor for cardiovascular disease selected from the Caja de Previsión Social from the University of Cartagena, 92% was found in the category without risk of no adherence, that is to say, that are adhered to the pharmacologic and nonpharmacologic treatments. This shows that the strategies to reach the patient and commit him/her with his/her own care have been effective to help improve significantly the adherence rates to pharmacologic and nonpharmacologic treatments.